Formação política no Movimento Nacional da Luta Antimanicomial (MNLA)/ Training Policy in National Anti-Asylum Movement (MNLA) - Rodrigues, Jeferson; Peres, Girlane Mayara (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2012)
RESUMO O artigo analisa em que medida o Movimento Nacional da Luta Antimanicomial, uma das tendências do movimento antimanicomial brasileiro, tem propiciado um espaço de formação política para os atores envolvidos. Trata-se de um estudo survey realizado com militantes desse movimento social, cuja referencia teórica é a ação coletiva de Alberto Melucci. Os resultados e conclusões indicam ausência de consenso sobre o conceito de formação política associado a instrumentos teórico-metodológicos para sua efetivação. ABSTRACT The article examines the extent to which the Anti-Asylum National Movement , one of the trends in Brazilian anti-asylum movement has provided a space for political training for the actors involved. This is a survey study conducted with social movement activists whose theoretical reference is the collective action of Alberto Melucci. The results and conclusions indicate absence of consensus on the concept of political formation associated with theoretical and methodological tools for its implementation. KEYWORDS: Social Movement; Mental Health; Formation.